Survey of Pesticide Use between Mango Farmers Practicing Area-Wide Integrated Pest Management and Conventional Farming in West Java, Indonesia - Sari, Riya Fatma; Subejo, Subejo; Suputa, Suputa; Vijaysegaran, Shanmugam; De Faveri, Stefano; Trisyono, Y. Andi (Universitas Gadjah Mada, 2024)
Mango farmers in Indonesia rely heavily on pesticides to control a variety of pests and diseases, with tephritid fruit flies being a major pest of the crop. To reduce pesticide use, Area-Wide Integrated Pest Management (AW-IPM) to control fruit flies was trialed and introduced in 2015 and has now been successfully implemented in several districts in West Java, Indonesia. This study surveyed pesticide use in mango farms adopting AW-IPM and those practicing conventional pest control methods. Purposive and Snowball sampling methods were used to select and interview 83 mango farmers to assess farmers knowledge and practices of pesticide use between the two groups. The farmers surveyed consisted of those that have adopted AW-IPM of fruit flies and conventional farmers, meaning those that did not adopt AW-IPM. The results of the survey revealed that compared to conventional farmers, the AW-IPM farmers had a high level of knowledge of pesticides and most of them were aware of pesticide-related environmental risks and adopted better and safer practices. Overall, storage of pesticides within living areas was reported by 10% of respondents, and most respondents (75%) adopted unsafe practices when disposing of used pesticide containers, such as selling them to plastic waste collectors. Half of all the respondents reported and experienced at least one symptom of a pesticide-related health problems. This study contributes to a better understanding of potential pesticide exposure and risks to mango farmers in Indonesia. A pesticide management training program for the mango farming community is badly needed.